내장형 비만과 피하지방형 비만 여성에 대한 자전거 운동 및 회복 시 지질대사의 변화 특성 - 이미선; Mi Sun Lee; 노호성; Ho Sung Nho (Ch'eyuk kwahak yŏn'gu, 2005)
비만 중에서도 내장지방이 과잉으로 축적된 내장형 비만은 질병과 관련이 깊기 때문에 지나친 내장 지방을 감소시키는 것이 중요하다. 내장지방을 감소시키는 것은 질병의 예방과 개선에 효과적이지만, 내장지방의 대사특성과 동물실험의 결과로부터 운동이 내장지방을 특이적으로 감소시키는 유효한 수단이라고 생각된다. 그러나 지금까지 운동이 내장지방을 특이적으로 감소시키는 가에 대해 명확한 결론은 없다. 따라서 내장지방형 비만 여성에 대한 AT수준의 일과성 운동(prolonged exercise) 및 회복 시 내장지방의 대사에 미치는 영향을 생리·생화학적지표의 변화로부터 운동에 대한 내장지방의 특이성을 검토하고자 하였다. 비만여대생 12명(19.7±2.9세)을 대상으로 CT촬영에 의해 내장지방형비만과 피하지방형비만으로 분류하여 40분간 일정부하의 자전거운동과 20분간의 회복시의 글루코스, 에피네프린, 놀에피네프린, 유리지방산, 인슐린, 렙틴의 생리적 반응을 검토하였다. 그 결과, 두 집단 모두 일정 시간이 경과함에 따라 호흡순환계의 생리학적 반응에 의한 놀에피네프린의 상승은, 특히 피하지방형비만군에서 안정시(98.6±50.7pg/ml)보다 20분경과시(341.5±172.7pg/ml), 40분경과시(363.1±100.8pg/ml)에 유의한 변화(p<.05)를 나타냈다. 혈중 Glucose 농도와 Leptin은 운동 중에 특이한 변화가 없었고, 양군 간에 차이도 보이지 않았지만, 혈중 Insulin농도는 운동시작 후 운동 종료 시까지 두 집단 모두 저하 경향을 나타냈다. 특히, 유리지방산의 상승효과가, 내장지방형비만군에서 회복기에 유의한 변화를 일으킨 것은 지금까지 선행 연구되어 알려진, 낮은 강도에서의 운동 중의 유리지방산 상승과 상이한 결과를 나타냈지만, 이러한 결과는 회복기에서의 지방연소 또한 비만개선에 있어서 중요한 시기라고 할 수 있다. It is important to reduce visceral fat because the obesity due to excess visceral fat is close relationship with various type of disease. The purpose of this study was to investigate characteristics of lipid metabolism during and after a bout of prolonged exercise performed at anaerobic threshold (AT) level in two types of obese women. Twelve obese women, aged 19.7±2.9 years, divided into two groups, I,e,, obese group due to excess visceral fat (VF group; n=6) and obese group due to excess subcutaneous fat (SF group; n=6). The subjects in the VF group had visceral fat area (VFA) over 100cm2and the VFA of the subjects in the SF group was lower than 100cm2. Oxygen consumption, respiratory exchange ratio, energy expenditure, blood glucose, epinephrine, norepinephrine, free fatty acids, insulin. and leptin were measured during a 40-min cycle ergometer exercise and during a 20-min recovery phase. Heart rate increased as time passed during the exercise in both groups. Increment in catecholamine occurred due to the physiological response in respiratory and circulatory systems was significant in the VF group. Energy expenditure due to the fat oxidation was higher in the VF group than the SF group. the results suggested that lipid metabolism during and after a bout of exercise performed at AT level was active and fat oxidation was higher in the VF group than the SF group. Therefore, the excercise performed at AT level as well as exercise at low intensity should have obtain attention by obese individuals.